Analysis of the Level of Adiponectin and Selected Cytokines in Patients with Knee Osteoarthritis - Iosif Ilia; Paula Diana Ciordas; Diana Nitusca; Alina Anton; Catalin Marian (Medicina, 2024)
Background and Objectives: Knee osteoarthritis (KOA) is a degenerative disease that is continuously targeting people of different ages, but especially the elderly population, the number of which tends to increase continuously at the global level. Apart from age, excess weight can influence the evolution of the disease, with obesity being associated with a weak inflammation stage and an imbalance between pro-inflammatory and anti-inflammatory cytokines. The present work aimed to analyze specific biomarkers, namely ACRP-30, IL-10, TNF-α, and IL-6, in knee synovial fluid, and correlate them with KOA patients’ clinical data, radiographic changes, and functional and pain scores. Materials and Methods: 24 subjects with KOA and over 50 years of age participate in the present study. Synovial fluid was harvested using ultrasound guidance from the target knees of the enrolled KOA patients, and the levels of ACRP-30, IL-10, TNF-α, and IL-6 were measured using enzyme-linked immunosorbent assays (ELISA). All patients underwent a supine X-ray at the target knee and were classified using Kellgren–Lawrence (K–L) grading. The Western Ontario and McMaster University Osteoarthritis Index (WOMAC) was used to assess self-reported physical function, pain, and stiffness. Results: The obtained results highlighted a significant correlation between age and adiponectin level (p = 0.0451, r = −0.412). Also, the IL-10 values are lower in cases where the intensity of the pain is more pronounced (p = 0.0405, r = −0.421). In addition, analyzing the data by gender, it was observed that in the case of males, stiffness is more related to age (p = 0.0079, r = 0.7993), compared to women (p = 0.0203, r = 0.6223). In the case of women, the progression of the disease tends to increase more intensively the WOMAC score’s total values (p = 0.00031, r = 0.8342), compared with men (p = 0.0289, r = 7013). Regarding interleukins and BMI, significant correlations were observed only in the case of men. Conclusions: A significant correlation between age and adiponectin, and adiponectin and IL-6, suggests that advanced age may contribute to adiponectin reduction. Comparing men with women, it was observed that men’s age is more related to rigidity, and IL-6 and IL-10 are directly correlated to BMI; in addition, women seem to be more sensitive to pain and stiffness.